Air and air-steam gasification of sewage sludge. The influence of dolomite and throughput in tar production and composition - Roche, Elena; de Andrés, Juan Manuel; Narros, Adolfo; Rodríguez, María Encarnación (Fuel (Guildford), 2014)
[Display omitted] •The effect of some primary measures on sewage sludge gasification products was tested.•Higher throughputs decreased the H2 content of the syngas and increased tar production.•The use of dolomite showed gravimetric tar removal efficiencies of up to 71%.•Dolomite performance remained fairly constant over the range of studied throughputs.•Under the tested experimental conditions, syngas dew point never dropped below 110°C. The influence of throughput (TR), steam and the use of dolomite (as primary catalyst) over the sewage sludge gasification products was investigated. For this purpose, experiments were conducted in an atmospheric fluidised bed reactor using air and air+steam as gasifying agents. The analysis of the results was mainly focussed on the gas composition, the gravimetric tar production, and the GC-detectable tar composition (and dew point estimations). According to the obtained results, higher TRs decreased the H2 content of the produced gas and clearly increased the gravimetric tar production. The use of air+steam, especially in the presence of dolomite, increased the H2 content (between 20% and 36%) and decreased the gravimetric tar production over all the tested TR, reaching tar removal efficiencies of up to 71%. Regarding the GC-detectable tar, higher TRs increased the heavy polyaromatic hydrocarbons production, steam slightly increased the water soluble tar content while the use of dolomite decreased the yield of all the tar classes except light aromatic hydrocarbons. Under the tested gasification conditions, the gas dew point never dropped below 110°C, value far above the recommended temperature when the syngas is to be used for engine applications.